Determinant of Qard: Evidence from Indonesian Islamic Rural Banks - Fitriyani, Yeny; Lidasan, Mussollini Sinsuat (UIN Salatiga, 2023)
This study was conducted to offer an assessment of the qard factors, concerning Indonesian Islamic Rural Banks. To conduct this analysis, data from Indonesian Rural Banks and macroeconomic panels were used. In addition, an approximated generalized method of the moment was also used to report qard determinants from 2012-2022. The results showed that Return on Assets (ROA), Bank Operational Costs to Operating Income (BOPO), and inflation negatively impacted the distribution of qard, while Non-Performing Financing (NPF) variable indicated a positive and significant impact. Valuable recommendations were formulated by comprehending the interplay between profitability ratios and macroeconomic conditions. These recommendations informed the development of products within the context of BPRS and Sharia banking, contributing to rural economic growth through qard financing. This study developed BPRS and Sharia banking products to increase rural economic growth. Qard financing served as an essential resource for individuals who did not meet the eligibility criteria of conventional banks. The adoption and expansion also promoted financial inclusion for marginalized communities.